The Mediating Role of Workplace Safety Climate on Safety Leadership and Safety Knowledge in Indonesian Petrochemical Employees - Sridadi, Ahmad Rizki; Himmawan, M. Fikri; Ninglasari, Sri Yayu; Fiqqih, Mohammad Nadhiful (The Journal of Behavioral Science, 2024)
Background/Problem: Effective safety leadership encompasses the capacity of authoritative figures to proactively steer and shape an organization through the adoption of safe practices and principles. Recognizing the pivotal role of leadership behavior in driving employee performance, particularly in facilitating collective bargaining, underscores its importance in organizational studies. Objective/Purpose: This study aimed to examine the mediation effect of workplace safety climate in the relationship between effective safety leadership and safety knowledge on performance within Indonesian petrochemical sector. Design and Methodology: Using a quantitative method, data was collected from 198 employees in an Indonesian petrochemical enterprise. Structural equation modeling with partial least squares method was employed for analysis. Results: The findings reveal that effective safety leadership (β = .48; p = .000) and workplace safety climate (β = .47; p = .000) significantly influence performance. A workplace safety climate mediates both the relationship between effective safety leadership (β = .13; p = .02) and safety knowledge (β = .33; p = .02) on performance. This workplace safety climate atmosphere emphasizes adherence to strict safety regulations for consistency. Conclusion and Implications: The study highlights the need for leaders to reevaluate training methodologies, focusing on enhancing safety knowledge and practical implementation. Strengthening a secure working environment is also emphasized for the well-being and protection of employees. This research contributes to the leadership climate literature by providing additional evidence that effective safety leadership and workplace safety climate can improve employee safety performance. Thus, top management can consider their leadership role during the process of achieving better employee safety performance.